2019
DOI: 10.1089/cap.2018.0166
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Quantitative Electroencephalography Demonstrates Differential Connectivity in Adolescents with Major Depressive Disorder

Abstract: Background: Biomarkers for psychiatric disorders in children and adolescents are urgently needed. This cross-sectional pilot study investigated quantitative electroencephalogram (qEEG), a promising intermediate biomarker, in pediatric patients with major depressive disorder (MDD) compared with healthy controls (HCs). We hypothesized that youth with MDD would have increased coherence (connectivity) and absolute alpha power in the frontal cortex compared with HC. Methods: qEEG was obtained in adolescents aged 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“… 50 As well, clinical reports examining low-frequency activity in MDD show inconsistent findings, possibly because sex was not used as an inclusive experimental variable. In support of our findings, clinical EEG studies showed increased global or frontal delta activity in people with MDD 52 54 and in women with menopausal depression. 55 Increased temporal theta and alpha power have also been associated with improved mood, 56 whereas a global cortical reduction in theta and alpha power has been reported in MDD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 50 As well, clinical reports examining low-frequency activity in MDD show inconsistent findings, possibly because sex was not used as an inclusive experimental variable. In support of our findings, clinical EEG studies showed increased global or frontal delta activity in people with MDD 52 54 and in women with menopausal depression. 55 Increased temporal theta and alpha power have also been associated with improved mood, 56 whereas a global cortical reduction in theta and alpha power has been reported in MDD.…”
Section: Discussionsupporting
confidence: 90%
“… 57 This reduced theta power in the occipitoparietal regions of patients with MDD may reflect impaired affect regulation and functional connectivity, 58 , 59 and indeed, cortical theta hypoconnectivity in MDD has been documented. 54 , 60 In preclinical studies, a genetic mouse model of depression also showed reduced baseline theta oscillatory power in the PFC, correlated with greater freezing time in the tail suspension test. 28 These findings demonstrating a link between reduced theta connectivity and MDD complemented our own results showing pathway-specific and temporal reductions in theta power in stress-susceptible rats, as well as increases in innate and stress-induced theta coherence in stress-resilient female and male rats, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Coherence showed a significantly reduced resting connectivity in the depressed patient in the delta, theta, alpha, and beta versus the healthy group, 11 and also in the other study, coherence showed this in the frontal cortex in the alpha and theta bands. 59 Synchronization likelihood in the delta and alpha frequency bands differentiated patients and controls, with the former exhibiting lower synchronization likelihood than the latter. 14 In Hu, 58 it was reported that the global phase synchronization index of the depressive patient had a much lower value compared with the healthy.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed increased cortical delta power and reduced theta power following mitragynine administration that was accompanied by increased neural activity, as indicated by increased c-fos expression in the PFC and Cg. Clinical EEG studies have documented increased global or frontal delta activity in depression patients (Bjork et al, 2008; McVoy et al, 2019; Morgan et al, 2005) as well as a global cortical reduction in theta and alpha power (Shim et al, 2018). In a preclinical study using a genetic mouse model system of depression, reduced theta power in the PFC was also observed, which directly correlated with greater freezing time in the tail suspension test (Sauer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%